Subjectivities and pedagogical intervention of Physical Education teachers in contexts of cultural diversity in the Puno-Peru region - Maquera-Maquera, Yanet Amanda (2021)
The new circumstances we live in have profoundly changed the ways of teaching and learning Physical Education (PE). The importance of a professor’s performance in the complexity of teaching is being questioned, and there is a permanent tension between the quality and relevance of pedagogical practices in PE. From a qualitative-hermeneutic methodology, this research aimed to understand the nature of the subjectivities and the pedagogical performance of PE teachers in contexts of cultural diversity. The narrative technique and in-depth interview were used with the teaching staff of the Professional School of Physical Education, at the National University of the Altiplano (UNA), and the Institute of Higher Education Pedagogical Public Physical Education-Lampa; the teachers were participating in the Program of Strengthening of Capacities-Ministry of Education of Peru 2019, in agreement with UNA-Puno. The following three categories were established for the analysis: self-reflection of pedagogical practice, pedagogical beliefs and actions, and coping with cultural diversity. The results achieved through the content analysis make it possible to understand that the subjectivities of PE teaching staff define the meanings given to their pedagogical performance. These meanings are generally characterized by the disagreement between experiential, pedagogical, and teaching knowledge, which are not very relevant to a context of predominant cultural diversity in the Puno region. There is a gap between what is and what is really done, so it is necessary to redefine PE teachers’ pedagogical performance of and incorporate their beliefs, thoughts, and attitudes from the contextualized historical-cultural singularity.